2008
DOI: 10.4049/jimmunol.181.1.785
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocyte Autoimmunity in Rheumatoid Synovitis Is Independent of Ectopic Lymphoid Neogenesis

Abstract: B lymphocyte autoimmunity plays a crucial role in the pathogenesis of rheumatoid arthritis. The local production of autoantibodies and the presence of ectopic lymphoid neogenesis in the rheumatoid synovium suggest that these dedicated microenvironments resembling canonical lymphoid follicles may regulate the initiation and maturation of B cell autoimmunity. In this study, we assessed experimentally the relevance of ectopic lymphoid neogenesis for B cell autoimmunity by a detailed structural, molecular, and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
98
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 67 publications
22
98
1
Order By: Relevance
“…In two large studies in established RA, large lymphocyte aggregates were found in around 30% of patients but did not associate with a clinical phenotype. 126,127 In early arthritis, the presence of lymphocyte aggregates did not predict an aggressive disease course and aggregates were rapidly diminished by several anti-rheumatic treatments. 119,128 Taken together, these studies suggest that lymphocyte aggregates are a pro-inflammatory phenomenon and not a persistent primary driver of synovitis.…”
Section: Cellular Compositionmentioning
confidence: 99%
“…In two large studies in established RA, large lymphocyte aggregates were found in around 30% of patients but did not associate with a clinical phenotype. 126,127 In early arthritis, the presence of lymphocyte aggregates did not predict an aggressive disease course and aggregates were rapidly diminished by several anti-rheumatic treatments. 119,128 Taken together, these studies suggest that lymphocyte aggregates are a pro-inflammatory phenomenon and not a persistent primary driver of synovitis.…”
Section: Cellular Compositionmentioning
confidence: 99%
“…Synovial tissue biopsy samples were processed and evaluated for lining layer thickness, vascularity, global inflammatory infiltration, and lymphoid aggregates, as described previously (35)(36)(37). Synovial tissues from the 158 RA patients were divided into 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the Ig V H gene was performed as described elsewhere (37,43). Ig V H and VDJ genes were amplified by PCR and ligated into the pGEM-T vector (Promega, Madison, WI) and transfected into Escherichia coli DH5␣.…”
Section: Methodsmentioning
confidence: 99%
“…An aggregate pattern was defined as the presence of inflammatory cells with a 20-cell diameter focus at least, if less, the pattern was considered as diffuse (16,17). The definition of aggregates includes both the aggregate and germinal center (GC)-like infiltrates (defined by the presence of follicular dendritic cells), since one of the aims of the study was to assess the degree of differentiation toward GC reactions to evaluate if the aggregate infiltrates have a biological or clinical relevance.…”
Section: Synovial Biopsiesmentioning
confidence: 99%